Construction of two-component chemically reactive supramolecular assemblies-acyl migration reactions in cocrystals of napthalene-2,3-diol and its diesters - Bahadur, Vir; Gonnade, Rajesh G.; Tamboli, I. Majid; Krishnaswamy, Shobhana; Shashidhar, Mysore S. (ChemPlusChem, 2021)
Reactions in solids are of contemporary interest due to applications in pharmaceutical industries to environmental sustainability. Although several reactive crystals that support chemical reactions have been identified and characterized, the same cannot be said about reactive cocrystals. Earlier we correlated the facile acyl group transfer reactions in crystals with supramolecular parameters obtained from the crystal structures. The structure-reactivity correlation revealed the requirement of proper juxtaposition of electrophile (C=O) and the nucleophile (OH) with distance (similar to 3.2 angstrom) and angle (similar to 90 degrees) along the chain structure. The current article describes the preparation of cocrystals that are capable of supporting intermolecular acyl group transfer reactions in a group of structurally similar molecules. The cocrystals of naphthalene 2,3-diol and its corresponding diesters showed a facile solid state acyl transfer reaction, which has been well correlated with their crystal structures.
Keywords: Acylation; domino reactions; intermolecular interactions; reaction in cocrystal; solid-state reactions; X-ray diffraction